How to draw cars the hot wheels way. - Robertson, Scott, 1966- (St. Paul (Minn.) : MBI, 2004)
This book provides excellent how-to-draw detail that is easy to follow for Hot Wheels[registered] and drawing enthusiasts from ages 10 to adult. Detailed drawing techniques with descriptive captions allow readers to create their own automotive designs. Author Scott Robertson combines drawing techniques and advice from Hot Wheels[registered] designers to create a book that artists and diecast car enthusiasts will love.
Keywords: Auto's.; Tekenen